Mitochondrial disorders and neurodegeneration - Schapira, Anthony (Henry Stewart Talks, 2007)
Spectrum of mitochondrial diseases, Mitochondrial metabolic pathway, MtDNA mutations and disease, Pathological features, MELAS, Genetic epidemiology of mtDNA mutations, Structural components of respiratory chain complexes, Mitochondrial DNA metabolism, Mitochondrial proteins and oxidative phosphorylation, Fatal mtDNA depletion syndrome, POLG mutations, Environmental influences on PD causation, PARK genes, Huntington's disease and mtDNA mutations, Genetic basis of Friedreich's ataxia, Mitochondrial toxins
Archived at 2019/07/30